2023
DOI: 10.1002/ps.7505
|View full text |Cite
|
Sign up to set email alerts
|

Arthropods on grapes benefit more from fungicide reduction than from organic farming

Abstract: BACKGROUND Pesticides are considered main contributors to global arthropod declines and therefore may decrease the provision of ecosystem services such as natural pest control. Organic farming and cultivating pest‐ and disease‐resistant varieties can allow pesticide applications and their impacts on nontarget organisms and the environment to be reduced. We investigated the effects of organic versus conventional management and fungus‐resistant versus susceptible wine grape varieties on arthropod biodiversity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 79 publications
0
3
0
1
Order By: Relevance
“…To prevent pathogen a acks on grapevines, products based on living microorganisms (biofungicides), bacterial derivatives, or botanicals, can be used as alternatives to synthetic fungicide applications [97]. Moreover, some studies have mentioned the planting of fungus-resistant varieties as a recommended approach to more sustainable viticulture [98][99][100]. The cultivation of these varieties led to the significant enhancement in the abundance of beneficial arthropods and predatory mite (Phytoseiidae and Tydeidae) density in both organic and conventional production types and contributed to the reduction of fungicide application [98,99].…”
Section: Evidence In Vineyard Systems On Fungicide Use Alternativesmentioning
confidence: 99%
See 1 more Smart Citation
“…To prevent pathogen a acks on grapevines, products based on living microorganisms (biofungicides), bacterial derivatives, or botanicals, can be used as alternatives to synthetic fungicide applications [97]. Moreover, some studies have mentioned the planting of fungus-resistant varieties as a recommended approach to more sustainable viticulture [98][99][100]. The cultivation of these varieties led to the significant enhancement in the abundance of beneficial arthropods and predatory mite (Phytoseiidae and Tydeidae) density in both organic and conventional production types and contributed to the reduction of fungicide application [98,99].…”
Section: Evidence In Vineyard Systems On Fungicide Use Alternativesmentioning
confidence: 99%
“…Moreover, some studies have mentioned the planting of fungus-resistant varieties as a recommended approach to more sustainable viticulture [98][99][100]. The cultivation of these varieties led to the significant enhancement in the abundance of beneficial arthropods and predatory mite (Phytoseiidae and Tydeidae) density in both organic and conventional production types and contributed to the reduction of fungicide application [98,99]. Pennington et al [100] reported enhanced densities of Lobesia botrana predators and reduced damage to inoculated grape bunches due to a reduction in fungicide applications in grapevine cultivars resistant to powdery and downy mildew.…”
Section: Evidence In Vineyard Systems On Fungicide Use Alternativesmentioning
confidence: 99%
“…La familia más abundante en este estudio fue Cicadellidae (19,82 %), la cual pertenece al GT de los herbívoros, y posee varias especies plagas de importancia en el cultivo de la papa (Costa & Lozada, 2010;Silva et al, 2019;Santos et al, 2020;Pérez et al, 2021). Al contrastar, lo que señala la literatura científica para Cicadellidae, se ha encontrado una alta mortalidad por efecto de diversos plaguicidas (Patel, 2022;Jawad & Nawar, 2023;Reiff et al, 2023), y una alta sensibilidad a la perturbación del suelo (Silva et al, 2019;Keil & Lozada, 2021). Opuestamente en este estudio la abundancia de Cicadellidae incrementó bajo la presencia del propineb, el cual fue 1,20 veces mayor que en el fipronil y 1,23 veces mayor que en el tratamiento convencional.…”
Section: Tratamientounclassified
“…This is especially relevant for agroecosystems (Michalko et al, 2019;Riechert, 1999). However, pesticide applications may affect this key role (Reiff et al, 2023;Theiling & Croft, 1988). Moreover, pesticides can unintentionally reach areas outside agroecosystems (Kaur & Garg, 2014) and may also affect other spider species along with the agrobiont spiders.…”
mentioning
confidence: 99%